Chemistry by number theory - Boeyens, Jan C. A.; Comba, Peter (Electronic structure and number theory, 2013)
Aspects of elementary number theory pertaining to the golden ratio and the golden spiral are shown to be related to and therefore of importance in the simulation of chemical phenomena. Readily derived concepts include atomic structure, electronegativity, bond order, the theory of covalent interaction and aspects of molecular chirality. The physical interpretation of the results implicates the 4D structure of space-time as a fundamental consideration. The implied classical nature of 3D molecular structure identifies molecular mechanics as an ideal method for structure optimization, based on parameters obtained by number theory. All results point at a 4D wave structure of electrostatic charge.